Dose-Response of High-Intensity Training (HIT) on Atheroprotective miRNA-126 Levels - Schmitz, Boris; Schelleckes, Katrin; Nedele, Johanna; Thorwesten, Lothar; Klose, Andreas; Lenders, Malte; Krüger, Michael; Brand, Eva; Brand, Stefan-Martin (Frontiers in Physiology, 2017)
Aim: MicroRNA-126 (miR-126) exerts beneficial effects on vascular integrity, angiogenesis and atherosclerotic plaque stability. The purpose of this investigation was to analyze the dose-response relationship of high-intensity interval training (HIIT) on miR-126-3p and -5p levels. Methods: Sixty-one moderately trained individuals (females = 31 [50.8%]; 22.0 ± 1.84 years) were consecutively recruited and allocated into three matched groups using exercise capacity. During a 4-week intervention a HIIT group performed three training intervals/week of 4 x 30 s at maximum speed (all-out), a progressive HIIT (proHIIT) group performed three training intervals/week of 4 x 30 s at maximum speed (all-out) with one extra interval every week (up to 7 x 30 s) and a low-intensity training (LIT) control group performed three training intervals/week for 25 min < 75% of maximum heart rate. Exercise miR-126-3p/ -5p plasma levels were determined using capillary blood from earlobes. Results: No exercise-induced increase in miR-126 levels was detected at baseline, neither in the LIT (after 25 min low-intensity running) nor the HIIT groups (after 4 min of high-intensity running). After the intervention, the LIT group presented an increase in miR-126-3p, while in the HIIT group, miR-126-3p levels were still reduced (all p < 0.05, pre- vs post-exercise). An increase for both, miR-126-3p and -5p levels (p < 0.05, pre- vs exercise) was detected in the proHIIT group. Between group analysis revealed that miR-126-3p levels after LIT and proHIIT increased by 2.12 ± 2.55 and 1.24 ± 2.46 units (all p < 0.01), respectively, compared to HIIT (-1.05 ± 2.6 units). Conclusions: LIT and proHIIT may be performed to increase individual miR-126 levels. HIIT without progression was less effective in increasing miR-126.